The dimensions of alliance portfolio configuration: A mediation model. (20th January 2015) - Castro, Ignacio; Roldán, José L; Acedo, Francisco J
Abstract: Our paper contributes to progress on the conceptualization and the operationalization of the alliance portfolio configuration. A variance-based structural equation modeling (partial least squares) has been applied to a sample made up of top global contractors. Previous works on alliance portfolio have analyzed the dimensions of alliance portfolio configuration independently and therefore, the interrelationships between them have not been studied. Results from the data analysis show that the dimensions of alliance portfolio configuration are interrelated in such a way that the relational and the partner alliance portfolio dimensions (a) fully mediate the effect of structural alliance portfolio on the value of the alliance portfolio capital; and (b) this capital exerts significant and positive influences on the growth of the international market share.